Pemanfaatan Metode Analytical Hierarchy Process (AHP) dalam Sistem Pendukung Keputusan untuk Seleksi Programmer - Rahmi, Lidya; Muchlis, Lita Sari; ., Iswandi; ., Adriyendi; Sari, Dewi Putri; Nadya, Rahma; Roofi, Ibnu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The recruitment process for programmers at the Tanah Datar District Communication and Information Office remains manual. Candidate evaluations are frequently performed without structured decision-making protocols, resulting in potential errors in identifying the most suitable applicants. This study seeks to develop a Decision Support System (DSS) employing the Analytical Hierarchy Process (AHP) methodology for the selection of programmers at the Tanah Datar District Communication and Information Office, by amalgamating hard-skill and soft-skill competencies. This study employs the Rapid Application Development (RAD) technique, comprising four phases: requirements planning, user design, building, and cutover. During the requirements planning phase, system needs are collected via interviews, documentation, and observation. This phase establishes the criteria, which encompass interviews (C1), application creation and design proficiency (C2), database and installation competencies (C3), and problem-solving skills (C4). During the user design phase, the system design is executed, followed by system development with PHP and MySQL in the building phase. In the cutover phase, system testing was performed utilizing the Computer System Usability Questionnaire (CSUQ) technique, yielding an average score of 86.74, which signifies that the system possesses commendable usability quality and is highly regarded by users. The research findings indicate that the AHP-based Decision Support System is successful in facilitating the selection process, expediting decision-making, and aiding agencies in identifying the most suitable applicants who fulfill the established criteria.